29.1k views
24 votes
Which expression is equivalent to 10x2 + (6x − 8x2) + 3 − (9x +4)?

1 Answer

11 votes

You are missing expression..

But if you simplify you can find the answer (given below)

Answer:


2x^2-3x-1

Explanation:


10x^2+\left(6x-8x^2\right)+3-\left(9x+4\right)


\mathrm{Apply\:rule}:\quad \:a+\left(b+c\right)=a+b+c


10x^2+\left(6x-8x^2\right)=10x^2+6x-8x^2


=10x^2+6x-8x^2+3-\left(9x+4\right)


\mathrm{Group\:like\:terms}


=-\left(9x+4\right)+10x^2-8x^2+6x+3


\mathrm{Add\:similar\:elements:}\:10x^2-8x^2=2x^2


=-\left(9x+4\right)+2x^2+6x+3


\mathrm{Apply\:the\:distributive\:law}:\quad \:-\left(a+b\right)=-a-b


-\left(9x+4\right)=-9x-4


=-9x-4+2x^2+6x+3


\mathrm{Group\:like\:terms}


=2x^2-9x+6x-4+3


\mathrm{Add\:the\:numbers:}\:-4+3=-1


=2x^2-9x+6x-1


\mathrm{Add\:similar\:elements:}\:-9x+6x=-3x


=2x^2-3x-1

Answer =
2x^2-3x-1

~Learn with Lenvy~

User Lmcarreiro
by
6.2k points